1999
DOI: 10.1017/s0022112099004450
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady ripple generation on steep gravity–capillary waves

Abstract: Parasitic ripple generation on short gravity waves (4 cm to 10 cm wavelengths) is examined using fully nonlinear computations and laboratory experiments. Time-marching simulations show sensitivity of the ripple steepness to initial conditions, in particular to the crest asymmetry. Significant crest fore–aft asymmetry and its unsteadiness enhance ripple generation at moderate wave steepness, e.g. ka between 0.15 and 0.20, a mechanism not discussed in previous studies. The maximum ripple steepness (in time)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The understanding of dissipation induced by breaking waves at various scales has been the topic of intensive research in recent decades, combining field work in the open ocean (Melville 1996;Melville & Matusov 2002;Veron et al 2008;Sutherland & Melville 2013), laboratory experiments on wave breaking (Melville & Rapp 1985;Tulin & Waseda 1999;Rapp & Melville 1990;Banner & Peirson 2007;Drazen et al 2008), and the dissipation induced by smaller scales involving surface tension, like micro-breaking, spilling breaking (Duncan et al 1999;Duncan 2001;Liu & Duncan 2003, 2006 and parasitic capillary waves (Perlin et al 1993;Jiang et al 1999;Caulliez et al 1998;Su 1982;Caulliez 2013). The importance of small scales, O(1 − 10) cm in the global ocean wave energy fluxes is still an open question and needs further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of dissipation induced by breaking waves at various scales has been the topic of intensive research in recent decades, combining field work in the open ocean (Melville 1996;Melville & Matusov 2002;Veron et al 2008;Sutherland & Melville 2013), laboratory experiments on wave breaking (Melville & Rapp 1985;Tulin & Waseda 1999;Rapp & Melville 1990;Banner & Peirson 2007;Drazen et al 2008), and the dissipation induced by smaller scales involving surface tension, like micro-breaking, spilling breaking (Duncan et al 1999;Duncan 2001;Liu & Duncan 2003, 2006 and parasitic capillary waves (Perlin et al 1993;Jiang et al 1999;Caulliez et al 1998;Su 1982;Caulliez 2013). The importance of small scales, O(1 − 10) cm in the global ocean wave energy fluxes is still an open question and needs further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Such breaking may result from the instability of parasitic capillary waves generated on the forward faces of short gravity-capillary waves (Duncan et al 1994(Duncan et al , 1999Duncan and Dimas 1999;Fedorov et al 1998;Jiang et al 1999;Perlin and Schultz 2000). Even in the absence of breaking, it has been shown that parasitic capillaries may lead to significantly enhanced radiation damping of longer gravitycapillary waves (Ruvinsky et al 1991;Longuet-Higgins 1995;Fedorov and Melville 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies have been for spatially and/or temporally periodic and steady flows. Solutions have been found, where under different conditions, ripples have been generated on the forward face of a propagating steep gravity wave (Longuet-Higgins [20,21], Jiang et al [22]), in the wave trough as in the steady solution of Schwartz and Vanden-Broeck [23] and symmetric ripple formation near the crest (Schultz et al [24]). The modal approach as presented in this paper can capture many of these details.…”
Section: Symmetric Sloshing In a Stationary Containermentioning
confidence: 99%